HUBUNGAN PENGETAHUAN DENGAN KESIAPAN IBU HAMIL DALAM MENGHADAPI PERSALINAN DI PRAKTEK BIDAN DI WILAYAH REJOSARI - Yulia Febrianita; Febrianti Zega (Jurnal Keperawatan Abdurrab, 2025)
High maternal and infant mortality rates are still a challenge in various countries, including Indonesia. One of the factors that influence the safety of the mother and baby in the birth process is the readiness of pregnant women in the face of labor. This readiness is greatly influenced by the level of mother's knowledge of labor, danger signs, and maintenance during and after delivery. Lack of information can cause anxiety and unpreparedness that is at risk of complications during childbirth. Therefore, this study aims to analyze the relationship between the level of knowledge of pregnant women and the readiness of mothers in dealing with labor in Midwifery Clinic, Rejosari Region. This study uses quantitative methods with descriptive correlation design. The research population is all pregnant women in Midwifery Clinis, as many as 32 people, who also became a sample with a total sampling technique. The research instrument uses a questionnaire, with data analysis carried out univariate and bivariate. The results of the analysis show that there is a significant relationship between the level of knowledge of pregnant women and the readiness of the mother in dealing with labor with the value of p-value = 0.01 (<α = 0.05). Based on the results of this study, it is recommended that pregnant women get further education regarding labor preparation through the class of pregnant women and health counseling. Health workers are also expected to be more active in providing information about labor signs, pain management techniques, as well as the importance of family support in the birth process. With increasing knowledge, it is expected that the readiness of pregnant women in the face of labor can increase, thereby reducing the risk of complications during labor.